Myanmar : Staff-Monitored Program. - International Monetary Fund. Asia and Pacific Dept. (Washington, D.C. : International Monetary Fund, 2013)
Myanmar is a low-income country, and with the right reforms, it can realize its rich economic potential. The government has embarked on a bold and historic set of reforms, which are already bearing fruit. Executive Directors support the steps for ensuring macroeconomic stability. Exchange rate unification will be an important foundational step for securing macroeconomic stability, which will help boost competitiveness and trade. A consistent monetary policy framework and containing fiscal deficits will give higher and stable revenues to fund development needs.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet